2021
DOI: 10.1109/access.2021.3065939
|View full text |Cite
|
Sign up to set email alerts
|

Designing Deep-Based Learning Flood Forecast Model With ConvLSTM Hybrid Algorithm

Abstract: Efficient, robust, and accurate early flood warning is a pivotal decision support tool that can help save lives and protect the infrastructure in natural disasters. This research builds a hybrid deep learning (ConvLSTM) algorithm integrating the predictive merits of Convolutional Neural Network (CNN) and Long Short-Term Memory (LSTM) Network to design and evaluate a flood forecasting model to forecast the future occurrence of flood events. Derived from precipitation dataset, the work adopts a Flood Index (), i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(48 citation statements)
references
References 35 publications
0
48
0
Order By: Relevance
“…The above results indicated that performance of ANFIS-GOA in terms of RMSE and WI value is prominent compared to hybrid ANN with KNN (Kan et al 2020); ANFIS-GA, ANFIS-PSO, ANFIS-ACO (Azad et al 2018); hybrid deep learning ConvLSTM (Moishin et al 2021); FSF-ARIMA (Banihabib et al 2020) and ANFIS (Rezaeianzadeh et al 2014).…”
Section: Assessment Of Outcome For Different Modelsmentioning
confidence: 80%
“…The above results indicated that performance of ANFIS-GOA in terms of RMSE and WI value is prominent compared to hybrid ANN with KNN (Kan et al 2020); ANFIS-GA, ANFIS-PSO, ANFIS-ACO (Azad et al 2018); hybrid deep learning ConvLSTM (Moishin et al 2021); FSF-ARIMA (Banihabib et al 2020) and ANFIS (Rezaeianzadeh et al 2014).…”
Section: Assessment Of Outcome For Different Modelsmentioning
confidence: 80%
“…Having the convolutional operation embedded inside the long short-term memory (LSTM) cell, it robustly extracts statistically significant antecedent lagged inputs from the predictive variables whilst the LSTM learns from the sequentially incorporated features for low latency predictions [18], [19]. Recently, convLSTM was applied for flood index forecasts [20] and precipitation forecasts [21], and these studies illustrated the superiority of convLSTM over the benchmarked counterparts. Being an intelligent and versatile predictive model, convLSTM is highly suitable for modeling cloud-affected UVI.…”
Section: Related Workmentioning
confidence: 99%
“…The ConvLSTM model was shown to outperform the traditional optical flow-based precipitation nowcasting model. Recent studies have shown that the ConvLSTM model can be successfully applied to predict future radar-based precipitation (Kim et al, 2017;Moishin et al, 2021).…”
Section: Convlstmmentioning
confidence: 99%
“…They showed that ConvLSTM can capture the spatiotemporal correlation between input rainfall image frames, which are recorded every 6 min across Hong Kong. Several studies have shown that the ConvLSTM architecture can be successfully applied to the precipitation nowcasting model (Kim et al, 2017;Moishin et al, 2021;Sønderby et al, 2020;Jeong et al, 2021). Although the convolution neural network (CNN) does not have a structure to conserve temporal information, Agrawal et al (2019) showed that a fully connected CNN called U-Net can make better predictions than traditional NWP models.…”
Section: Introductionmentioning
confidence: 99%